The Impact of Legalized Abortion on Crime - Donohue, J. J.; Levitt, S. D. (Quarterly Journal of Economics, 2001)
We offer evidence that legalized abortion has contributed significantly to recent crime reductions. Crime began to fall roughly eighteen years after abortion legalization. The five states that allowed abortion in 1970 experienced declines earlier than the rest of the nation, which legalized in 1973 with Roe v. Wade. States with high abortion rates in the 1970s and 1980s experienced greater crime reductions in the 1990s. In high abortion states, only arrests of those born after abortion legalization fall relative to low abortion states. Legalized abortion appears to account for as much as 50 percent of the recent drop in crime.